2017
DOI: 10.3141/2643-16
|View full text |Cite
|
Sign up to set email alerts
|

Origin–Destination-Based Travel Time Reliability

Abstract: Travel time reliability (TTR) is an important performance indicator for transportation systems. TTR can be generally categorized as either segment based or origin–destination (O-D) based. A primary difference between the two TTR estimations is that route information is implied in segment-based TTR estimations. Segment-based TTR estimations have been widely studied in previous research; however, O-D–based TTR estimations are used infrequently. This paper provides detailed insight into O-D–based TTR estimations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…In order to evaluate OD, it is necessary to set various indexes to evaluate passengers' behaviors quantitatively. Yang S used taxi GPS data to estimate OD travel time, which helps to analyze the route preference of passengers [14]. Margaretic P applied the spatial economic flow model and characteristic function spatial filtering method to air transportation, and discussed the impact of departure destination on air passenger flow [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to evaluate OD, it is necessary to set various indexes to evaluate passengers' behaviors quantitatively. Yang S used taxi GPS data to estimate OD travel time, which helps to analyze the route preference of passengers [14]. Margaretic P applied the spatial economic flow model and characteristic function spatial filtering method to air transportation, and discussed the impact of departure destination on air passenger flow [15].…”
Section: Introductionmentioning
confidence: 99%
“…Direction and stations of Nanjing metro lines 15,14,13,12,11,10,9,8,7,6,5,41,42,43,44,45,46,47,48,49,50,. 51, 52, 53, 54, 55] …”
mentioning
confidence: 99%
“…Comparison studies are limited, though. In [13], the authors concluded that there were no significant differences between O-D-based and route-based estimates in most part of the studied time periods. In [14], the researchers found that adding an alternative path tends to decrease the O-D-based TTR.…”
Section: Introductionmentioning
confidence: 86%
“…), there are some other TTR measures, such as travel time variability (TTV), planning travel time index (PI), and buffer index (BI). Among these measures, BI has been widely utilized in existing literature [7,8,13,27,28] and as concluded in [29] has a high consistency with the coefficient of variation and thus is best suitable for the measure of TTR. e authors adopted the idea and took BI as the primary TTR measure.…”
Section: Measures Of Travel Timementioning
confidence: 99%
“…Each hidden traffic state was represented by a Gaussian distribution. Using Gaussian mixture distributions to model travel-time distribution is reasonable because previous studies (e.g., Yang et al 2017;Yang and Wu 2016;Jenelius and Koutsopoulos 2015;Feng et al 2014;Guo et al 2011) have shown that they can effectively determine travel-time distributions when traffic is heterogeneous. Hofleitner and Bayen's algorithm (2011) then used numerical optimization methods to achieve optimized TTD.…”
Section: Previous Studies and Problem Statementmentioning
confidence: 99%